Exposure of Malaysian children to air pollutants over the school day - Ezani, Eliani; Brimblecombe, Peter (Multidisciplinary Digital Publishing Institute, 2022)
Children are sensitive to air pollution and spend long hours in and around their schools, so the school day has an important impact on their overall exposure. This study of Kuala Lumpur, Selangor and its surroundings assesses exposure to PM2.5 and NO2, from travel, play and study over a typical school day. Most Malaysian children in urban areas are driven to school, so they probably experience peak NO2 concentrations in the drop-off and pick-up zones. Cyclists are likely to receive the greatest school travel exposure during their commute, but typically, the largest cumulative exposure occurs in classrooms through the long school day. Indoor concentrations tend to be high, as classrooms are well ventilated with ambient air. Exposure to PM2.5 is relatively evenly spread across Selangor, but NO2 exposure tends to be higher in areas with a high population density and heavy traffic. Despite this, ambient PM2.5 may be more critical and exceed guidelines as it is a particular problem during periods of widespread biomass burning. A thoughtful adjustment to school approach roads, design of playgrounds and building layout and maintenance may help minimise exposure.